Training of Kurikulum Merdeka Teaching Module Using Experiential Learning Cycle in Physics MGMP - Ermawati, Imas Ratna; Tri Isti Hartini; Sugianto; Nuraeni Nanda Sari; Sekar Tyas Widyanti; Putri Sri Wahyuni; Mardiana Ningsih (Universitas Pendidikan Ganesha, 2024)
Most of the Physics Subject Teacher Conference (MGMP) teachers need help understanding the making of the Merdeka Curriculum teaching module and still depend on lesson plans from the 2013 Curriculum. This hinders the implementation of the new curriculum designed to improve teaching quality. This study aims to analyze the independent curriculum teaching module using the experiential learning cycle in the physics MGMP. This study uses a qualitative-descriptive research method with a participatory research design. The research subjects involved 15 physics teachers from MGMP who participated in the two-day training, totalling 16 lesson hours. Data were collected through observation, interviews, and questionnaires, with instruments in the form of interview guides and questionnaires. Data analysis was conducted using the thematic analysis method. The results showed that 88% of the participants considered the material discussed very important, and 90% expressed great satisfaction with the training method. This study concludes that training is efficacious in improving teachers' understanding and skills in developing teaching modules relevant to the Merdeka Curriculum. The implication of this research is the need for continuous development of training programs to support the implementation of the new curriculum and improve the overall quality of education.